Effects of modified starch and fat on the rheological characteristics of newly formulated processed cheese: Use of experimental design method. Issue 5 (4th May 2017) - Benaouadj, Fella; Ziane-Zafour, Amel Hadj; Rebiha, Mounia
ABSTRACT: This study aims to investigate the impact of the incorporation of starch (modified and non-modified) on the texture of the processed cheese in order to appreciate a new recipe on one hand and to try to reduce fat content (FC) on the other. The modeling of the experimental results has been performed. An experimental design was used (the variable factors are the amount of starch and FC). The dry extract (DE) of cheese and parameters derived from the modeling of rheological results are the selected responses. The cheese with a concentration of modified starch that is greater than 2% has a high viscosity at rest, while the cheese with non-modified starch has a lower viscosity. When the FC exceeds 15%, the viscosity increases as the concentration of the starch exceeds 2%. Below this concentration, the FC effect is negligible except when the starch concentration is 1%, in this case the viscosity decreases. GRAPHICAL ABSTRACT: